Genome-wide evaluation of gene editing outcomes using CRISPR/Cas9 in seed propagated Camelina sativa and vegetatively propagated Solanum tuberosum - Jayakody, Thilani B.; Zarka, Daniel; Cho, Keun Ho; Jensen, Jacob; Sikora, Samantha; Buell, C. Robin; Douches, David S.; Nadakuduti, Satya Swathi (Frontiers in Plant Science, 2024)
CRISPR/Cas9 is the most popular genome editing platform for investigating gene function or improving traits in plants. The specificity of gene editing has yet to be evaluated at a genome-wide scale in seed-propagated Camelina sativa (L.) Crantz (camelina) or clonally propagated Solanum tuberosum L. (potato). In this study, seven potato and nine camelina stable transgenic Cas9-edited plants were evaluated for on and off-target editing outcomes using 55x and 60x coverage whole genome shotgun sequencing data, respectively. For both potato and camelina, a prevalence of mosaic somatic edits from constitutive Cas9 expression was discovered as well as evidence of transgenerational editing in camelina. CRISPR/Cas9 editing provided negligible off-target activity compared to background variation in both species. The results from this study guide deployment and risk assessment of genome editing in commercially relevant traits in food crops.